The Concept of a Tramp according to Jack Kerouac - Svitáková, Eliška (Univerzita Pardubice, 2020)
This bachelor thesis focuses on the tramp lifestyle that Jack Kerouac depicted in his novel On the Road. The theoretical part provides information about the Beat Generation and explores the lifestyle of the Beat authors. The practical part analyses Kerouac's depiction of the tramp characters and explores the opposition to consumerist society. The last chapter also considers and compares other similar tramp lifestyles.
Kult tuláka podle Jacka Kerouaca
Keywords: tuláci; Kerouac, Jack; Beatnická generace; konzumní společnost; tramps; Kerouac, Jack; Beat Generation; consumerist society